The Effect of Project Based Learning on Students’ Motivation and Mathematics Learning Outcomes in Kurikulum Merdeka at the Elementary School Level - Asna Mardin; Hadiyanto Hadiyanto; Melva Zainil; Nurhizrah Gistituati; Azrul Azrul; Ary Kiswanto Kenedi (AT-TA'LIM, 2024)
This study aims to investigate the effect of the Project Based Learning (PjBL) model on students’ motivation and mathematics learning outcomes in the context of Kurikulum Merdeka at the elementary school level. Learning mathematics in a mechanical way, without engaging students in communicating and constructing their understanding, often leads to superficial comprehension. In the current era of advanced technology, student engagement should ideally be enhanced. However, the Covid-19 pandemic negatively impacted students’ motivation to learn. This research is a quasi-experimental study conducted in the first semester of the 2022/2023 academic year involving two classes. The hypothesis was tested using the t-test with a significance level of 5% (? = 0.05). The results showed that the t-value for learning motivation was 2.614 and for learning outcomes was 5.368, both of which exceeded the critical t-table value of 2.04. These findings indicate that the use of the Project Based Learning model has a significant positive effect on both student motivation and mathematics learning outcomes in the implementation of Kurikulum Merdeka. The implications of this study suggest that incorporating PjBL into mathematics instruction can enhance students’ intrinsic motivation and deepen their understanding of mathematical concepts through real-world application. For educators, especially within the Kurikulum Merdeka framework, this model offers a practical and student-centered approach that supports the development of critical thinking, collaboration, and problem-solving skills. Policymakers and curriculum developers are encouraged to support the integration of PjBL through teacher training and resource development to optimize learning outcomes at the elementary level.